Estudio retrospectivo de la incidencia de distomatosis ( Fasciola hepatica) en un Centro de Faenamiento de Ecuador. - Pujos Aranda, Julio César (2021)
Dystomatosis is a liver disease caused by the fluke Fasciola hepatica present in species such as cattle, sheep and pigs, its infection is related to poor conditions in the food ingested by the host. The incidence of distomatosis generates economic losses in the agricultural productive sector, for which it is necessary to carry out a retrospective study to determine the prevalence of this disease in bovine species. The objective of this research is to present a retrospective study of the prevalence of distomatosis (Fasciolasis hepatica) in the Saquisilí Slaughter Center, on the economic losses obtained from the seizure of infected bovine livers. The research area is Microbiology, Parasitology, Immunology and Animal Health within the detection of emerging diseases in ruminants. The study population is in cattle slaughtered between the periods 2016 to 2020, analyzing the daily records of the slaughterhouse under study. The prevalence percentage of dystomatosis is 7.65% / year and its incidence is statistically significant on the amount by weight (kg) of livers seized with an annual average of 5182.74 kg, and the economic losses that reach $ 8085.08 /anus. In conclusion, the retrospective study in the Camal Tecnológico de Saquisilí shows that if there is an incidence between dystomatosis and the economic losses that it generates in agricultural producers, therefore it is recommended to design contingency plans that allow reducing the percentage of prevalence of this sickness.